Using a hybrid model to evaluate development strategies for digital content - Yeh, Ching-Chiang (Technological and Economic Development of Economy, 2017)
Digital content (DC) is one of the most important areas of growth within the global creative and knowledge-based economy. The paper aims to propose a systematic approach to evaluating strategies to develop DC industry and how it should be effectively implemented. Our analysis employs a hybrid multiple criteria decision making (MCDM) approach by using the interpretive structural modelling (ISM) method to deal with the interrelationship among criteria, and the analytic network process (ANP) method is employed to determine the relative weights of each criterion. Finally, in order to choose the alternative for the ideal solution of this problem, a technique for order performance by similarity to ideal solution (TOPSIS) is used. To demonstrate the validity of this method, the Taiwan’s DC industry is used as an illustrative case. The study generates results that can serve as a reference for decision-makers in the formulation of their development strategies for DC. Moreover, the evaluation model constructed in this study goes beyond existing measures and may serve as a reference for a decision-maker.First published online: 02 Nov 2015